Solar PV Policy, Barriers and Proposed Solution for Technical Barriers in Thailand - Chatthaworn, Rongrit; Angaphiwatchawal, Pikkanate; Chaitusaney, Surachai (International Journal of Engineering and Technology, 2018)
This paper presents solar PV history in Thailand consisting of installation target, incentive schemes, procurements and barriers for supporting the coming of solar PV. For the barrier viewpoint, one of the most significant barriers is the technical power system problem; especially, voltage violation and system loss increase when high capacity of solar PV is installed in the system. Therefore, electric utilities usually determine the capacity limitation criterion of solar PV for each electrical feeder which can delay the growth of solar PV installation. Consequently, this paper presents the method to solve this barrier in order to maximize the installation of solar PV in Thailand. The method is based on the construction of typical distribution feeders with various levels of solar PV penetration and locations. The three scenarios based on solar PV locations: clustered near the beginning of feeder, clustered near the middle of feeder, and clustered near the end of feeder are simulated. The considered constraints are voltage limitation and system loss. The modified distribution system is used to test the proposed method which is simulated by DIgSILENT PowerFactory software. The results show that the proposed method provides the solution that can support more solar PV installation than capacity limitation criterion determined by distribution utilities.Â Â